Sistem Pendeteksi Stres pada Manusia Menggunakan Metode Fuzzy Logic Berbasis Internet of Things - Irmayanti; Hasmina Tari Mokui; Wa Ode Siti Nur Alam (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2022)
Stress is the body's response to stressors. One way to detect whether someone is experiencing stress is by using electronic devices. The purpose of this study is to design and evaluate the performance of stress detection systems in humans using the Internet of Things (IoT)-based Fuzzy Logic Method. The Fuzzy logic implemented in this system applies the Fuzzy Mamdani Rule with three input parameters sourced from the Galvanic Skin Response Sensor, Ear Clip Heart Rate Sensor and LM35DZ Sensor. In addition, this stress detection system utilizes two types of microcontrollers, i.e. Arduino Nano and Arduino Wemos. The output of this stress detection system is displayed on the liquid crystal display and can be accessed on android applications, providing easy access remotely and showing stress levels in a wider range. Based on the performance evaluation of the stress detection system when calibrated using Matlab Software, the obtained average error and accuracy rate are 7.5% and 92.5% respectively. Thus, this stress detection system has good accuracy and performance. Keyword — Mamdani Fuzzy Logic; Internet of Things; Microcontroller, Sensors, Stress.